Nuclear Phosphatidylinositol-Phosphate Type I Kinase α-Coupled Star-PAP Polyadenylation Regulates Cell Invasion - A.P., Sudheesh (Mol Cell Biol, 2018)
Star-PAP, a nuclear phosphatidylinositol (PI) signal-regulated poly(A) polymerase (PAP), couples with type I PI phosphate kinase α (PIPKIα) and controls gene expression. We show that Star-PAP and PIPKIα together regulate 3′-end processing and expression of pre-mRNAs encoding key anti-invasive factors (KISS1R, CDH1, NME1, CDH13, FEZ1, and WIF1) in breast cancer. Consistently, the endogenous Star-PAP level is negatively correlated with the cellular invasiveness of breast cancer cells. While silencing Star-PAP or PIPKIα increases cellular invasiveness in low-invasiveness MCF7 cells, Star-PAP overexpression decreases invasiveness in highly invasive MDA-MB-231 cells in a cellular Star-PAP level-dependent manner. However, expression of the PIPKIα-noninteracting Star-PAP mutant or the phosphodeficient Star-PAP (S6A mutant) has no effect on cellular invasiveness. These results strongly indicate that PIPKIα interaction and Star-PAP S6 phosphorylation are required for Star-PAP-mediated regulation of cancer cell invasion and give specificity to target anti-invasive gene expression. Our study establishes Star-PAP–PIPKIα-mediated 3′-end processing as a key anti-invasive mechanism in breast cancer.